Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1590/s0104-42302006000400023
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida em portadores de doença arterial coronária: comparação entre gêneros

Abstract: Subjects who underwent surgical treatment had the most favorable evolution. Men when compared to women had a better quality of life in the beginning of treatment with a progressive improvement after six and twelve months, while women, after an improvement at six months, presented a decrease at twelve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
20

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 5 publications
1
11
0
20
Order By: Relevance
“…por isso, manifestarem-se principalmente em pessoas com idade mais avançada. 6 Vários autores afirmam que a prevalência do tratamento cirúrgico em pacientes cardíacos se dá no sexo masculino, 6,9,[11][12] assim como nesta pesquisa, pois o sexo masculino se mostra mais resistente em procurar o serviço e não dá a devida atenção ao seu verdadeiro estado de saúde. 6 Outro ponto a ser considerado, é que ser homem constitui um fator de risco para doenças cardiovasculares.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…por isso, manifestarem-se principalmente em pessoas com idade mais avançada. 6 Vários autores afirmam que a prevalência do tratamento cirúrgico em pacientes cardíacos se dá no sexo masculino, 6,9,[11][12] assim como nesta pesquisa, pois o sexo masculino se mostra mais resistente em procurar o serviço e não dá a devida atenção ao seu verdadeiro estado de saúde. 6 Outro ponto a ser considerado, é que ser homem constitui um fator de risco para doenças cardiovasculares.…”
Section: Resultsunclassified
“…9,11,14 Talvez isso possa explicar por que a maioria dos pacientes depende da ajuda do governo, visto que, em razão da baixa escolaridade, o sujeito tende a trabalhar em atividades que exigem maior esforço físico e, por causa do ato cirúrgico, os pacientes, muitas vezes, são impedidos de voltar a realizar tais atividades.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…In our country, Favorato et al 14 described a higher degree of QoL impairment in women with CAD after clinical or surgical treatment or percutaneous coronary intervention (PCI), when compared to men. These results were consistent with the Rita-2 study 15 , which included a large sample and also identified the female sex as a factor associated with QoL impairment in patients with CAD.…”
Section: Introductionmentioning
confidence: 96%
“…The concern with the concept of "quality of life" comes to rescue broader aspects than symptom control, reduced mortality or increased life expectancy. The quality of life related to health refers to a subjective view of the patient about their health status, and may be contrasted with physiological assessments with clinical interpretations relating to the patient welfare and their functional capacity [13,14].…”
Section: Introductionmentioning
confidence: 99%